1995
DOI: 10.1021/bi00045a027
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of pp60c-src Tyrosine Kinase Activities Using a Continuous Assay: Autoactivation of the Enzyme Is an Intermolecular Autophosphorylation Process

Abstract: A continuous assay for pp60c-src tyrosine kinase (srcTK) was developed. A lag in phosphorylation of the peptide RRLIEDAEYAARG was observed that could be eliminated by preincubation with MgATP. The induction time for this lag was dependent upon MgATP and srcTK concentrations. When autophosphorylation was monitored by 32P incorporation from [gamma-32P]ATP, a lag in the time course was also observed. These results demonstrate that autoactivation is an intermolecular process. The electrospray ionization mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
203
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(215 citation statements)
references
References 39 publications
8
203
0
Order By: Relevance
“…This result further demonstrates that the lack of time-dependent complete inactivation of Yes Ya by Csk is the result of autophosphorylation. Furthermore, these results indicate that the autophosphorylation that blocks Csk inactivation is on the main autophosphorylation site within the activation loop of Yes and Src, although other sites have been reported to also undergo autophosphorylation in the Src family (Osusky et al, 1995;Barker et al, 1995;Jullien et al, 1994). This result also indicates that autophosphorylation will likely have the same function in modulating Csk regulation of other PTKs in the Src family.…”
Section: Resultsmentioning
confidence: 75%
“…This result further demonstrates that the lack of time-dependent complete inactivation of Yes Ya by Csk is the result of autophosphorylation. Furthermore, these results indicate that the autophosphorylation that blocks Csk inactivation is on the main autophosphorylation site within the activation loop of Yes and Src, although other sites have been reported to also undergo autophosphorylation in the Src family (Osusky et al, 1995;Barker et al, 1995;Jullien et al, 1994). This result also indicates that autophosphorylation will likely have the same function in modulating Csk regulation of other PTKs in the Src family.…”
Section: Resultsmentioning
confidence: 75%
“…Our results agree with data presented by others who showed that the Src tyrosine kinase retains activity when phosphorylated on Tyr-416 and Tyr-527 (41). 3 Previous work in our laboratory as well as kinetic data by other groups suggest that the activating phosphorylation of Tyr-394 in Src family members is an intermolecular event rather than intramolecular reaction (22,(42)(43)(44). 4 Intermolecular phosphorylation of Tyr-394 may be carried out by Lck in vivo, but it is quite possible that other Src family members, or non-Src tyrosine kinases, may also act to phosphorylate Tyr-394 and activate Lck.…”
Section: Discussionmentioning
confidence: 98%
“…The availability of a low level of c-Src kinase activity in resting cells (13) and the increasing association of ER46 with E2 stimulation (Fig. 3A) may favor homotypic (26,27) and heterotypic (24,25) protein interactions with c-Src and further enforce c-Src ''opening.'' Indeed, it has been demonstrated that doubly phosphorylated c-Src can be active, such that Y419 phosphorylation can override the p-Y530-directed inhibition (28).…”
Section: Vehicle) (C and D)mentioning
confidence: 99%